Acoustic analysis of intonation: Comparison between two dialects of Spanish from the north of the peninsula - Ballesteros Panizo, Mapi; Font-Rotches, Dolors (Lingua, 2019)
This paper introduces the melodic characterisation of spontaneous Spanish presented by speakers from two regions in the north of Spain: Asturias and Navarre, based on a conversational corpus composed of 100 utterances emitted by 62 participants. It focuses on the intonation of the dialects, an aspect which is poorly investigated but highly relevant for characterising and distinguishing one from the other. The study is based on the Melodic Analysis of Speech method, a meticulous acoustic analysis through which exact values are obtained from spontaneous speech, which can then be compared. In short, the most notable coincident and divergent melodic features between the two dialects are: (1) the tendency of the two to present a first peak, more frequently tonic in Asturian Spanish and atonic in Navarrese; (2) an almost flat or slightly falling body of the contour with abundant internal inflections, which are also distinguished by the syllable where the rise ends: tonic in Asturian Spanish, and tonic and atonic in the final position of the word in Navarrese; and (3) more pronounced final inflections, with five different endings, and tonal fields, in the region of Navarre. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: intonation; Spanish; dialects; Navarrese; Asturian Spanish; JCR; Scopus